KESALAHAN EJAAN BAHASA INDONESIA PADA SURAT DINAS DI KANTOR CAMAT SIULAK MUKAI KABUPATEN KERINCI - Yoga Karmizi; Hasnul Fikri; Gusnetti - (Jurnal Bahasa Indonesia Prima (JBIP), 2023)
The purpose of research on Indonesian spelling errors in official letters at the Siulak Mukai sub-district office is to describe errors in punctuation marks and letters. The background of this research is that there are still many errors in using Indonesian spelling in writing official letters at the Siulak Mukai district office. The type of research used is qualitative research with descriptive methods. The data source is official letters issued by the Siulak Mukai sub-district office in 2020 for the January–December period of 25 letters. The data collection technique was carried out through observation and document analysis techniques. Data analysis techniques consist of two activities simultaneously, namely data reduction and data presentation. From the analysis carried out on 25-letter data, it was found that there were errors in using dots in 23-letter data, or 92% of errors. Errors in using commas amount to as many as 14 data letters, or 56% of errors. Slash mark errors can be as high as 10 letters, or 40% of the time. Hyphen error amounts to as much as one letter of data or a 4% error. Capital letter errors accounted for 21 letters or 84% of all errors. Italics errors are as common as four-letter data, accounting for 16% of all errors. The error in using bold letters is four, or 16% of the time.